Qualidade de vida relacionada com a saúde, aptidão física, índice de massa corporal e dieta mediterrânica em adolescentes. - Olga Sofia Ferreira Evaristo (2018)
ABSTRACT Adolescence represents an important stage of life for the development of healthy behaviors. The aims of this thesis were: i) to analyze the associations between body mass index (BMI) and health-related quality of life (HRQoL) and exploring the potential mediation effect of cardiorespiratory fitness (CRF) on the relationship between BMI and HRQoL, in adolescents (study I);; ii) to analyze the combined associations of CRF and muscular fitness with HRQoL and to assess the differences between HRQoL score across groups of cardiorespiratory fitness and muscular fitness (study II);; iii) to explore the independent and combined associations between physical fitness and adherence to the mediterranean diet with HRQoL (study III);; and iv) to explore the longitudinal association between CRF and HRQoL over time and to determine whether changes in CRF were associated with HRQoL over a two-year follow-up period (study IV). Research was conducted using three cross-sectional studies and one longitudinal study involving 957 (study 1), 567 (study 1), 956 (study 3) and 571 (study 4) Portuguese adolescents ages 12-18 years. Body weight and height were measured according to standard protocols. BMI was classified according to the cut-off points defined by the International Obesity Task Force. HRQoL was measured using the Kidscreen-10 questionnaire. Physical fitness was assessed with the ALPHA health-related fitness battery. Socioeconomic status was assessed using the Family Affluence Scale. Accelerometers were used to obtain objective data about time spent in physical activity. Pubertal stage was assessed using the Tanner Scale. Adherence to Mediterranean diet was assessed using the KIDMED Index. In Study I, girls had a higher prevalence of overweight and obesity. HRQoL scores were slightly lower in girls. HRQoL was inversely and significantly associated with BMI in both sexes. CRF was qualified as a full mediator on the association between BMI and HRQoL in both sexes. In Study II, both CRF and muscular fitness were positively associated with HRQoL. Adolescents with high CRF and high muscular fitness showed better HRQoL. Study III, shows that high adherence to mediterranean diet and high physical fitness level were significantly and positively associated with higher HRQoL scores. In Study IV, CRF was positively associated with HRQoL at baseline and at the follow-up. Participants with persistent high CRF over a two-year period showed the highest scores for HRQoL at follow-up. HRQoL and CRF declined significantly from baseline to follow-up. These findings re-emphasize the importance of targeting public health programmes aimed to tackle high rates of overweight and obesity as well to increase PF levels, and adherence to Mediterranean diet, as an integral part of a health-enhancing lifestyle and adolescents quality of life.